Cerebrospinal fluid and its physiology. Issue 12 (December 2016) - Puntis, Michael; Reddy, Ugan; Hirsch, Nicholas
Abstract: This article describes the anatomy and physiology of cerebrospinal fluid and the abnormalities that can result in hydrocephalus.